Specification for radio disturbance and immunity measuring apparatus and methods. Radio disturbance and immunity measuring apparatus. Antenna calibration sites and reference test sites for 5 MHz to 18 GHz Part 1-5, (2nd October 2020) - British Standards Institution
No abstract available